PENDANAAN PEMBANGUNAN, DEGRADASI LINGKUNGAN DAN KONFLIK DALAM PENGELOLAAN SUMBER DAYA ALAM - Mita Noveria (Masyarakat Indonesia, 2012)
Natural resource extractions can generate economic bene? ts for some countries. The income generated can ? nance their developments programs, such as for human resources development. The bene? ts from natural resource extractions also ? ow to companies that have the right for managing the resources. For these companies, the economic bene? ts from natural resource extraction are often returned to communities using corporate social responsibility (CSR) programs. Unfortunately, for some countries, natural resource extractions create negative impacts due to overexploitation. Unsustainable natural resource extractions often caused social con?icts as people, compete for rent seeking. Frequently, these con?icts involved citizens against the government. In order to sustain the bene? ts from the natural resources extractions, the government and the community should manage the resources with full consideration of their sustainability.